SYNTHESIS, CHARACTERIZATION, CYTOTOXICITY AND ANTIMCIROBIAL STUDIES OF METAL(II) COMPLEXES OF SCHIFF BASE DERIVED FROM 2- BENZOYLBENZOIC ACID AND 1,3-DIAMINOPROPANE - SANI, UMAR; DAYYIB, AISHA S.; ABUBAKAR, SAMAILA; ADAM, DAILAMI S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Metal complexes of Ni(II), Cu(II) and Zn(II) with a Schiff base derived from 2-benzoylbenzoic acid and 1,3-diaminopropan have been prepared and characterized. Infrared spectral studies reveal that Schiff base behaves as a neutral tetradentate ligand and coordinates to the metal ions via the two azomethine nitrogen and carboxylate oxygen. Molar conductance measurement of (7.97 – 29.46) ohm-1 cm2 mol-1 indicates a non-electrolytic nature of all the complexes. Solubility test showed that all complexes and Schiff base are soluble in DMSO and methanol. Magnetic susceptibility and IR studies suggests tetrahedral structure for the complexes while Job’s method of continues variation establish 1:1 metal to ligand ratio, on which basis the coordination structures are proposed. The in vitro antibacterial and antifungal activity showed that the complexes are more active than the Schiff base. Moreover, the cytotoxicity analysis indicates that the tested compounds possess low toxicity.